2001
DOI: 10.1267/ahc.34.423
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Morphology and Neuropeptide Immunoreactivity of Superior Cervical Ganglion Neurons that Innervate the Major Salivary Glands in Rats.

Abstract: A neuronal tracer, WGA-HRP, was injected into the rat parotid gland (PG), submandibular gland (SMG), and sublingual gland (SLG) to label the superior cervical ganglion (SCG) neurons, and the number, size of soma, dendritic arborization and immunoreactivities (IR) of vasoactive intestinal polypeptide (VIP) and neuropeptide Y (NPY) were investigated. The number and size of neurons projecting into SMG were greater than those of neurons projecting into the PG or SLG. The PG and SLG projecting neurons did not show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 55 publications
1
2
0
Order By: Relevance
“…Upper cervical ganglion neurons projecting onto the submandibular gland, the largest organ, were largest. This finding agrees with the current theory, but no significant difference was observed in the size of upper cervical ganglion neurons projecting onto the parotid and sublingual glands, although the tissues were significantly different in size (Miyauchi et al ., 2001; Asamoto, 2004; Fig. 9d).…”
Section: Correlation Between the Cell Body Size Of Upper Cervical Gansupporting
confidence: 92%
See 1 more Smart Citation
“…Upper cervical ganglion neurons projecting onto the submandibular gland, the largest organ, were largest. This finding agrees with the current theory, but no significant difference was observed in the size of upper cervical ganglion neurons projecting onto the parotid and sublingual glands, although the tissues were significantly different in size (Miyauchi et al ., 2001; Asamoto, 2004; Fig. 9d).…”
Section: Correlation Between the Cell Body Size Of Upper Cervical Gansupporting
confidence: 92%
“…. whether the cell body of upper cervical ganglion neurons projecting on a large target organ is large, and that of neurons projecting on a small target organ is small’ (Miyauchi et al ., 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The human SCSGs neurons, of different size and number, contain different neuropeptides: neuropeptide Y (NPY), vasoactive intestinal polypeptide (VIP), calcitonin gene-related peptide (CGRP), somatostatin (SOM), etc., ( Baffi et al, 1992 ; Miyauchi et al, 2001 ). Analysis and comparison of NPY immunoreactivity of SCSG neurons in the rat indicated that NPY-positive neurons were smaller than NPY-negative neurons at more distal position in the SCSG, close to the external carotid nerve ( Headley et al, 2005 ).…”
Section: Discussionmentioning
confidence: 99%